Characterization and perceptual interaction of key aroma compounds in Rosa roxburghii Tratt by sensomics approach - Xiaofang Sheng; Xin Li; Xinxin Lu; Xiaohui Liu; Weiyuan Tang; Zhihai Yu; Xiaozhu Liu; Fei Zhang; Qun Huang; Mingzheng Huang (Food Chemistry: X)
Rosa roxburghii Tratt (RRT) is esteemed for its unique aroma and nutritional value. Analyzing RRT juice samples from four elevations using GC–MS and GC-O, 99 volatile compounds were identified with 37 exhibiting aroma activity. 29 compounds including aldehydes, alcohols, and terpenes, were key contributors to RRT's aroma, based on high OAVs. Aroma recombination and omission tests confirmed 18 key aroma compounds in RRT while 2,5-Dimethyl-4-methoxy-3(2H)-furanone, hexanal, furfuryl acetate, furaneol acetate, and benzaldehyde as critical aroma compounds. The σ-τ graph revealed additive interactions among primary aroma compounds, indicating synergistic effects on RRT's overall aroma profile. Longli produced the most fragrant RRT at the lowest elevation of the four producing areas.